The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/ic000990p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an NH−π Interaction in Co(III) Ternary Complexes with Aromatic Amino Acids

Abstract: The NH-pi interaction has been detected in the crystal structures of Co(III) ternary complexes with N,N-bis(carboxymethyl)-(S)-phenylalanine (BCMPA) and aromatic amino acids including (S)-phenylalanine ((S)-Phe), (R)-phenylalanine ((R)-Phe), and (S)-tryptophan ((S)-Trp)). Additionally, this interaction has been studied in solution for Co(III) ternary complexes with BCMPA or NTA (NTA = nitrilotriacetic acid) and several amino acids (AA) by means of electronic absorption, circular dichroism (CD), and (1)H NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 45 publications
(37 reference statements)
3
25
0
Order By: Relevance
“…Spectroscopic measurements and X-ray crystal structures have indicated that the side chain is constrained to the equatorial plane for both complexes. [41] The spectroscopic and electrochemical data are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic measurements and X-ray crystal structures have indicated that the side chain is constrained to the equatorial plane for both complexes. [41] The spectroscopic and electrochemical data are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[41] The CD spectral data for (S) )). [41] In the case of (R)-1, only the band near 610 nm, originating from a transition attributable to the chiral site, is inverted relative to that of (S)-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ligands coordinated to a metal, can interact with a π-system. In addition, interactions named metal-ligand-aromatic cation-π interactions (MLACπ) [14][15][16][17][18][19], can be considered as a type of XH/π hydrogen bond [20][21][22]. It was shown that some of these interactions are among the strongest XH/π hydrogen bonds [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although NH···π interactions in proteins have been known since 1984, [15] in complexes of transition metals they have been discovered only recently [16] as, because of their low interaction energy, [17,18] they are difficult to detect in solution. One of the best ways to identify the presence of NH···π interactions in aqueous solution is the anomalous chemical shift of the NH protons involved in the interaction.…”
Section: Introductionmentioning
confidence: 99%